2021
DOI: 10.3390/ijms22042211
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Active Site Residues of the Siderophore Synthesis Enzyme PvdF and Evidence for Interaction of PvdF with a Substrate-Providing Enzyme

Abstract: The problematic opportunistic pathogen Pseudomonas aeruginosa secretes a siderophore, pyoverdine. Pyoverdine scavenges iron needed by the bacteria for growth and for pathogenicity in a range of different infection models. PvdF, a hydroxyornithine transformylase enzyme, is essential for pyoverdine synthesis, catalysing synthesis of formylhydroxyornithine (fOHOrn) that forms part of the pyoverdine molecule and provides iron-chelating hydroxamate ligands. Using a mass spectrometry assay, we confirm that purified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Interestingly, Gasser and colleagues [ 63 ] showed, using the FRET–FLIM (Förster resonance energy transfer measured by fluorescence lifetime microscopy) technique, that PvdA interacts physically with PvdJ, PvdI, PvdL, and PvD, suggesting the presence of a strongly organized multienzymatic complex coordinating the PVD biosynthesis. Similarly, Philem and collaborators [ 64 ] demonstrated the fundamental role played by PvdF through a mutagenesis experiment, as the mutants carrying the inactivated enzyme had a reduced production of PVDI. Therefore, the authors suggest a possible switch to regulate PVD production for biotechnological purposes.…”
Section: Pvd Biosynthesismentioning
confidence: 97%
See 1 more Smart Citation
“…Interestingly, Gasser and colleagues [ 63 ] showed, using the FRET–FLIM (Förster resonance energy transfer measured by fluorescence lifetime microscopy) technique, that PvdA interacts physically with PvdJ, PvdI, PvdL, and PvD, suggesting the presence of a strongly organized multienzymatic complex coordinating the PVD biosynthesis. Similarly, Philem and collaborators [ 64 ] demonstrated the fundamental role played by PvdF through a mutagenesis experiment, as the mutants carrying the inactivated enzyme had a reduced production of PVDI. Therefore, the authors suggest a possible switch to regulate PVD production for biotechnological purposes.…”
Section: Pvd Biosynthesismentioning
confidence: 97%
“…As just mentioned, two other NRPSs directly involved in the elongation of the peptide are PvdJ and PvdD, catalyzing the addition of L-Lys, L-hfOrn, and two L-Thr residues [ 63 , 64 , 65 ]. The activity of two auxiliary enzymes, PvdG and MbtH, appears to be required for the intra-cytoplasmic maturation of the ferribactin.…”
Section: Pvd Biosynthesismentioning
confidence: 99%
“…Two other contributions to this Special Issue concern iron acquisition via siderophores in P. aeruginosa . The paper by Philem et al [ 8 ] investigated the role of PvdF, a hydroxyornithine transformylase enzyme, in the synthesis of pyoverdine, the siderophore with the highest affinity for iron among those synthesized by this opportunistic pathogen. Through a mass spectrometry assay, their study confirmed the predicted activity of the enzyme.…”
mentioning
confidence: 99%